Three essays of applied economics : superstar effect, taxation and workers' mobility, penalties and deterrence - (:unkn) unknown (Università della Calabria, 2021)
This thesis is composed of three distinct essays, aiming at studying three different phenomena, highly relevant in the economic literature: the phenomenon of the superstar effect, the relationship between the levels of taxation and the mobility of workers across countries or regions, the deterrence resulting from the tightening of laws in a given legal system. The thesis is made up of three chapters. First of all, collecting data from the American basketball championship (NBA), we are able to show the importance of the phenomenon called "Superstars Effects" in the determination of players' wages. In the second chapter, taking into consideration the United States of America, we determine, through the use of Multinomial Logit Models, how the different levels of taxation in the different US states affect the choice of where to play by the players of the NBA championship. Finally, the third chapter examines the impact of the introduction of Law no. 41/2016 in Italy (the law introducing the crime of "Vehicular homicide"), on the number of accidents and on the main forms of driving offences involved in the introduction of the law, through the use of a Regression Discontinuity Design.
Dottorato di Ricerca in Scienze Economiche ed Aziendali. Ciclo XXXIII
Keywords: Superstar; Wage; Mobility; Taxation; Deterrence